Analysis of Determinants Related to Stunting in Toddlers in the Working Area of the Buntulia Community Health Center, Pohuwato Regency - Nur Istiqoma Suja; Sunarto Kadir; Vivien Novarina A. Kasim (Universitas Negeri Gorontalo, 2026)
Introduction: Stunting is a health problem and associated with the risk of illness and death, suboptimal brain development, resulting in impaired motor and mental growth. Gorontalo Province ranks 12th out of 38 provinces, where Pohuwato District has a stunting prevalence of 18.4% among toddlers. Several variables can influence the incidence of stunting in children, including nutritional intake, infectious diseases, food availability, feeding patterns, and environmental sanitation. This study aims to assess the relationship between nutritional intake, infectious diseases, food availability, feeding patterns, and environmental sanitation with the incidence of stunting in Buntulia Community Health Center working area.Method: The study was conducted at the Buntulia Community Health Center using quantitative methods with cross sectional approach. A sample of 272 toddlers was obtained using the Slovin formula. The data analysis used logistic regression consisting of univariate, bivariate and multivariate method.Results: 91.2% of the toddlers did not experience stunting. Regarding individual determinants, 81.1% of the subjects had insufficient nutritional intake, while 89.3% had no history of infectious diseases. Household food security was observed in 57.4% of cases, yet 87.1% of toddlers exhibited inadequate dietary patterns. Additionally, 93.8% of respondents maintained good environmental sanitation. The results of the multivariate model revealed that nutritional intake (95% CI: 0.00) and dietary pattern (95% CI: 0.00) were significant predictors, while food availability (95% CI: 0.15) showed a broader confidence interval in relation to the incidence of stunting.Conclusion: Only food availability are associated with stunting in the Buntulia Community Health Center working area. Keywords: Environmental sanitation, feeding patterns, food availability, nutritional intake, stunting